Agomelatine or ramelteon as treatment adjuncts in glioblastoma and other M1- or M2-expressing cancers - Kast, Richard E. (Contemporary Oncology/Współczesna Onkologia, 2015)
The impressive but sad list of over forty clinical studies using various cytotoxic chemotherapies published in the last few years has failed to increase median survival of glioblastoma beyond two years after diagnosis. In view of this apparent brick wall, adjunctive non-cytotoxic growth factor blocking drugs are being tried, as in the CUSP9* protocol. A related theme is searching for agonists at growth inhibiting receptors. One such dataset is that of melatonin agonism at M1 or M2 receptors found on glioblastoma cells, being a negative regulator of these cells’ growth. Melatonin itself is an endogenous hormone, but when used as an exogenously administered drug it has many disadvantages. Agomelatine, marketed as an antidepressant, and ramelteon, marketed as a treatment for insomnia, are currently-available melatonin receptor agonists. These melatonin receptor agonists have significant advantages over the natural ligand: longer half-life, better oral absorption, and higher affinity to melatonin receptors. They have an eminently benign side effect profile. As full agonists they should function to inhibit glioblastoma growth, as demonstrated for melatonin. A potentially helpful ancillary attribute of melatonergic agonists in glioblastoma treatment is an increase in interleukin-2 synthesis, expected, at least partially, to reverse some of the immunosuppression associated with glioblastoma.